Analysing the Russia-Ukraine Conflict from Liberal and Realist Perspectives - BEREBON, Charles (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
The international world has been confronted with a substantial problem in the form of the continuing war between Russia and Ukraine, which started in February 2022. The origins of the conflict may be attributed to events occurring in 2014. Nevertheless, a multitude of narratives have emerged around the conflict, with some portrayals casting Russia in an antagonistic light, while others present the United States and NATO as the instigators of the war. The continuing conflict has considerable significance within the realm of international relations theory since it represents a notable threat to the established liberal international order, which has endured for a considerable period of time. This essay aims to study the Russia-Ukraine situation through the lens of two prominent international relations theories: realism and liberalism. This study will provide a concise examination of the two dominant theories and their respective interpretations and justifications of the crisis. The issue is also seen as a resurgence of the Cold War inside the global system. This essay aims to examine a realist’s perspective on the continuing conflict by analysing its key assumptions and providing insights from both realist and liberal viewpoints. Realists attribute the outbreak of conflict to the perceived threat posed to their respective nations’ security resulting from the growth of NATO and the European Union. Conversely, liberals see the primary risk as emanating from an illiberal Russia. The study elucidates several facets of the two theories and their respective explications of the conflict. In conclusion, it may be argued that realism provides a more comprehensive framework for understanding the Russia-Ukraine conflict compared to liberalism, hence placing liberalism at a disadvantage in terms of explanatory power.